2014
DOI: 10.4172/2165-7092.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Carcinoma with the First Symptom of Acute Pancreatitis: MRI Findings and Clinical Features

Li Y2,
et al.

Abstract: To study the MRI findings and clinical features of pancreatic carcinoma with the first symptom of acute pancreatitis. Materials and Methods:Twelve patients with pancreatic carcinoma and the first symptom of acute pancreatitis were included in this study. Pancreatic carcinoma with acute pancreatitis was confirmed by pathology. The MRI findings and clinical features of pancreatic carcinoma combined with acute pancreatitis were noted.Results: In the 12 patients with acute pancreatitis, the pancreas appeared edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was found that there is a very close and complex relationship between liver and pancreas, that's why the liver function of most of the patients with pancreatic carcinoma was abnormal. Previous studies showed that pancreatic carcinoma can cause acute pancreatitis, in which apoptosis of the pancreatic acinar cells releases trypsin, further promoting the release of a large number of inflammatory cytokines that cause liver injury [11,12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there is a very close and complex relationship between liver and pancreas, that's why the liver function of most of the patients with pancreatic carcinoma was abnormal. Previous studies showed that pancreatic carcinoma can cause acute pancreatitis, in which apoptosis of the pancreatic acinar cells releases trypsin, further promoting the release of a large number of inflammatory cytokines that cause liver injury [11,12,13] .…”
Section: Discussionmentioning
confidence: 99%